Pan-Cancer Analysis, Reveals COVID-19-Related BSG as a Novel Marker for Treatment and Identification of Multiple Human Cancers - Huang, Tao; He, Wei-Ying (Frontiers in Cell and Developmental Biology, 2022)
Background: Coronavirus disease 2019 (COVID-19) has been a public treat and healthcare concern caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. During the period of the pandemic of COVID-19, cancer patients should be paid more attention, as more severe events are found on cancer patients infecting SARS-CoV-2. Basigin (BSG) is an essential factor for the infection and progression of COVID-19 and tumorigenesis of multiple tumors, which may serve as a novel target for the effective treatment against COVID-19 and multiple human cancers. Methods: A total of 18,911 samples from multiple centers were included in our research for the comprehensive investigation of the differences in BSG expression between human organs, cancer cells, cancers tissues, and normal tissues. Cox regression analysis and Kaplan-Meier curves were utilized to explore the prognosis factor of BSG in cancers. Correlation analyses were used to determine associations of BSG expression with tumor mutational burden, the immune microenvironment, etc. Gene set enrichment analysis was applied to explore the underlying mechanisms of BSG in cancers. Results: Compared with normal tissues, BSG expression was highly expressed in 13 types of cancers (cholangiocarcinoma, etc.) and lowly expressed in colon adenocarcinoma and rectum adenocarcinoma. BSG expression was related to the prognosis of eight cancers (e.g., breast invasive carcinoma) (p < .05). The gene also demonstrated a pronounced effect in identifying 12 cancers (cholangiocarcinoma, etc.) from their control samples (AUC > 0.7). BSG expression was associated with DNA methyltransferases, mismatch repair genes, immune infiltration levels, tumor mutational burden, microsatellite instability, neoantigen, and immune checkpoints, suggesting the potential of BSG as an exciting target for cancer treatment. BSG may play its role in several cancers by affecting several signaling pathways such as drug cytochrome metabolism P450 and JAK-STAT.